FENOMENOLOGI MINAT PEMBELIAN TIKET KONSER PASCA PANDEMI: WAR TICKET KONSER COLDPLAY JAKARTA TAHUN 2023 - Rizky Harisnanda; Wiji Setiawan; Rini Sudarmanti (Lafadz Jaya Publisher, 2023)
This study aims to analyze the phenomenon of the Coldplay concert ticket war in Jakarta in 2023 and the factors that influence consumer behavior in buying expensive concert tickets. The method used in this study is a qualitative approach by using interview techniques, and document analysis to collect data. The data is then analyzed systematically and interpretively to identify the themes, models, and contexts that emerge from the phenomena studied. The results of the study show that the war ticket phenomenon for the Coldplay concert in Jakarta in 2023 is the result of consumer behavior which is influenced by factors such as the desire to meet social needs, the desire to experience a unique experience, and the influence of social media in creating awareness and interest in the concert. Consumer behavior in buying expensive concert tickets can also be associated with the concept of consumptive behavior, in which individuals tend to behave consumptively in an effort to fulfill their wants and needs. In dealing with the phenomenon of concert ticket wars, it is important for concert organizers and marketers to understand the factors that influence consumer behavior in buying concert tickets. This can be done by increasing awareness through social media, creating unique appeal, providing clear information about concerts and tickets, and involving consumers in promoting concerts to others.